The Erosive wear of elastomers - Arnold J C; Hutchings I M (Journal of Natural Rubber Research, 1991)
The erosive wear of a range of unfilled elastomers (predominantly natural rubber) due to the impact of small hard particles was investigated. Removal of material was determined to be due to the growth of fatiuge cracks into the bulk of the material, under conditions of both glancing impact (where there are considerable similarities with abrasion by a smooth indenter) and normal impact. The influence on erosion of the impact conditions and of the mechanical properties of the elastomers was investigated, and some success was achieved in formulating theoretical models for the erosion process. Comparison of the erosive wear rates of a range of elastomers showed that a soft, unfilled natural rubber vulcanisate exhibited the highest resistance to erosive wear by silica particles.
Keywords: Elastomers; Erosive Wear